Gas turbine engineering handbook - Boyce, Meherwan P. (Oxford : Butterworth-Heinemann, 2011)
Written by one of the field's most well known experts, the Gas Turbine Engineering Handbook has long been the standard for engineers involved in the design, selection, maintenance and operation of gas turbines. With far reaching, comprehensive coverage across a range of topics from design specifications to maintenance troubleshooting, this one-stop resource provides newcomers to the industry with all the essentials to learn and fill knowledge gaps, and established practicing gas turbine engineers with a reliable go-to reference. This new edition brings the Gas Turbine Engineering Handbook right up to date with new legislation and emerging topics to help the next generation of gas turbine professionals understand the underlying principles of gas turbine operation, the economic considerations and implications of operating these machines, and how they fit in with alternative methods of power generation. The most comprehensive one-stop source of information on industrial gas turbines, with vital background, maintenance information, legislative details and calculations combined in an essential all-in-one reference Written by an industry-leading consultant and trainer and suitable for use as a training companion or a reliable dip-in guide Includes hard-won information from industry experts in the form of case histories that offer practical trouble-shooting guidance and solutions.
Chapter 1: Overview of Gas Turbines -- Chapter 2: Theoretical and Actual Cycle Analysis -- Chapter 3: Compressor and Turbine Performance Characteristics -- Chapter 4: Performance and Mechanical Standards -- Chapter 5: Rotor Dynamics -- Chapter 6: Centrifugal Compressors -- Chapter 7: Axial-Flow Compressors -- Chapter 8: Radial-Inflow Turbines -- Chapter 9: Axial-Flow Turbines -- Chapter 10: Combustors -- Chapter 11: Materials -- Chapter 12: Gas Clean Up System -- Chapter 13: Bearings and Seals -- Chapter 14: Gears -- Chapter 15: Lubrication -- Chapter 16: Spectrum Analysis -- Chapter 17: Balancing -- Chapter 18: Couplings and Alignment -- Chapter 19: Control Systems and Instrumentation -- Chapter 20: Gas Turbine Performance Test -- Chapter 21: Maintenance Techniques -- Chapter 22: Case Studies -- Appendix: Equivalent Units.
Previous ed.: Boston, Mass.: Gulf Professional Pub., 2006.
Includes bibliographical references and index.
Keywords: Gas-turbines.; Electronic books